The Incidence Rate of Breast Cancer in Suleimani Governorate in 2006: Preliminary Study - Hussein, Ali Hattem; Aziz, Peri Mohammad (Sulaimani Journal for Pure and Applied Sciences, 2009)
Background: Breast cancer is the most common site-specific cancer in women. The incidence rate of breast cancer in Suleimani did not estimated before the year 2006. The aim of this study is to find out the incidence rate of breast cancer and some other statistical data in Suleimani city / Iraq in 2006. Patients and Methods: A questionnaire was designated to collect data from all newly diagnosed breast cancer patients in the year 2006, and from control group. We set up a hypothesis that to be tested using Chi- Square test at 95% confidence level. Results: The number of patients was 61 (60 females and 1 male). The incidence rate in females is 10.1 per 100000 adult females in the year 2006. The age group of highest incidence is 45 – 54. Most of patients are house wives, married, fertile, living in city center and urban areas, have no family histories of breast carcinoma, nonsmokers, have history of breast feeding, have body mass index above normal range, and mammography or U/S was infrequent screening test for breast mass done for them. Invasive ductal carcinoma of breast is the most frequent tumor among patients. The results revealed that 11 (18.0%) of patients have history of exposure to chemical weapons in the year 1988. Conclusion: The incidence rate of breast cancer in Suleimani is 10.1 per 100000 adult females in the year 2006, which is relatively low incidence.
Keywords: Breast cancer; Suleimani city; incidence rate; 2006; mammography; risk factors